Mental Health in Anesthesiology and ICU Staff: Sense of Coherence Matters - Schäfer, Sarah K.; Lass-Hennemann, Johanna; Groesdonk, Heinrich; Volk, Thomas; Bomberg, Hagen; Staginnus, Marlene; Brückner, Alexandra H.; Holz, Elena; Michael, Tanja (Frontiers in Psychiatry, 2018)
Hospitals, and particularly intensive care units (ICUs), are demanding and stressful workplaces. Physicians and nurse staff are exposed to various stressors: emergency situations, patients’ deaths, and team conflicts. Correspondingly, several studies describe increased rates of PTSD symptoms and other mental health problems in hospital staff. Therefore, it is important to identify factors that lower the risk of psychopathological symptoms. High levels of sense of coherence (SOC) and general resilience as well as an internal locus of control (LOC) have already been identified as important health-benefitting factors in medical staff. The current study aimed to evaluate their unique impact in an ICU and an anesthesiology unit. The cross-sectional online survey investigated SOC, LOC, general resilience, general mental health problems as well as PTSD symptoms in nurses and physicians within an ICU and an anesthesiology unit (N = 52, 65.4% female). General mental health problems were assessed using the ICD-10-Symptom-Rating (ISR) and PTSD symptoms were measured using the PTSD Checklist for DSM-5 (PCL-5). The Sense of Coherence Scale (SOC-L9) assessed SOC, the Resilience Scale (RS-11) measured general resilience, and LOC was determined using a 4-item scale for the assessment of control beliefs (IE-4). As expected, SOC, r = -.72 p < .001, general resilience, r = -.46, p < .001, and internal LOC, r = -.51, p < .001, were negatively correlated with general mental health problems while an external LOC showed a positive association, r = .35, p = .010. However, in a multiple regression model, R2 = 53.9%, F(4, 47) = 13.73, p < .001, only SOC significantly predicted general mental health problems by uniquely accounting for 13% of the variance. For PTSD symptoms, which were highly correlated with general mental health problems, a similar pattern of results was found. SOC was found to be the most important correlate of both general mental health problems and PTSD symptoms in an ICU and an anesthesiology unit. Thus, if further evidenced by longitudinal studies, implementing interventions focusing on an enhancement of SOC in training programs for ICU and anesthesiology unit staff might be a promising approach to prevent or reduce psychopathological symptoms.